Suppression of Sirtuin-1 Increases IL-6 Expression by Activation of the Akt Pathway During Allergic Asthma - Lingling Tang; Qingge Chen; Ziyu Meng; Li Sun; Linyun Zhu; Jinjin Liu; Junsheng Hu; Zhenhua Ni; Xiongbiao Wang (Cellular Physiology and Biochemistry, 2017)
Background/Aims: A growing number of studies have demonstrated that the activity and expression level of sirtuin-1 (SIRT1) are decreased in asthma patients; however, the mechanisms underlying decreased SIRT1 expression and function are still not completely understood. Interleukin (IL)-6 plays important roles in inflammation during allergic asthma. In this study, we examined whether loss of SIRT1 activity regulated the expression of IL-6 and further verified the underlying mechanisms. Methods: The human airway epithelial cell line 16HBE was used to test the effects of the SIRT1 inhibitor (salermide) on expression of IL-6. IL-6 mRNA and protein expression were assessed with real-time polymerase chain reaction (PCR), immunochemistry, and ELISA. OVA-challenged mice were used as an asthma model to investigate the effect of SIRT1 activation on IL-6 and relative Akt phosphorylation level. Results: We found that inhibition of SIRT1 increased IL-6 mRNA and protein levels in a time-dependent manner, which was accompanied by increased Akt pathway activation in 16HBE cells. Furthermore activation of Akt showed upregulated expression of the IL-6 protein whereas Akt inhibitor, LY294002 or Akt siRNA significantly inhibited SIRT1-regulated IL-6 expression. Conversely, activation of SIRT1 inhibited Akt activation and IL-6 expression in an asthmatic mice model and 16HBE cells. Conclusion: Our results indicate the potential role of SIRT1 in regulating inflammation by modulation of IL-6 expression in an Akt-dependent manner during allergic asthma.